"I randomize, therefore I think": Computational indeterminacy and the tensions of liberal subjectivity among writers of computer‐generated poetry in the United States. (13th January 2023) - Wilf, Eitan
Abstract: Scholars have theorized the use of chance processes in modern art in general, and in computer‐based art in particular, as the expression of an aesthetics of nonintention and authorial abnegation. Although writers of computer‐generated poetry in the United States make extensive use of computer‐based randomization, their creative adventures with computational indeterminacy do not lead them to endorse an aesthetics of nonintention or authorial abnegation. Rather, they cultivate different forms of authorial intentionality and pursue different and often‐conflicting goals. These tensions result from computational indeterminacy's affordances in relation to the different and often‐conflicting cultural currents that inform contemporary US liberal subjectivity. These currents include calls to advance social justice and inclusivity; an emphasis on self‐determination; a willingness to approach technology as an inscrutable, autonomous, and self‐determining form of creative agency; and the celebration of rarefied aesthetic abstraction and experimentation as a form of expressive freedom.